Development of Oil Prices and its Impact on Inflation - Krkošková, Magdalena; Pikhart, Zdeněk; Hladík, Miroslav; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
The purpose of the thesis is to observe relationship between the development of oil price and the rate of inflation. Oil is one of the main inputs in the economy, and, therefore, the price change influences the aggregate supply and macroeconomic indicators, such as inflation. The aim is to analyze whether there is a positive relationship between the price of oil and inflation. Theoretical part of the thesis is concentrated on the theory of inflation, its components and way of measurements. Furthermore, there is discussed chronological development of oil prices and the relationship between oil prices and inflation. Practical part is based on the econometric model used in order to testify the dependence of inflation on the price of oil. There are used quarterly data of the United States of America collected from the U.S. Energy Information Administration and Federal Reserve Bank of St. Louis from January 1986 to March 2014. The final part discusses the results of four used models and meeting of aims.
Vedoucí práce: Zdeněk Pikhart
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses